COLOSTOMY CLOSURE: RISK FACTORS FOR COMPLICATIONS - FONSECA,Alexandre Z. (2017)
ABSTRACT Background : The restoration of intestinal continuity is an elective procedure that is not free of complications; on the contrary, many studies have proven a high level of morbidity and mortality. It is multifactorial, and has factors inherent to the patients and to the surgical technique. Aim : To identify epidemiological features of patients that underwent ostomy closure analyzing the information about the surgical procedure and its arising complications. Method : It was realized a retrospective analysis of medical records of patients who underwent ostomy closure over a period of seven years (2009-2015). Results : A total of 39 patients were included, 53.8% male and 46.2% female, with mean age of 52.4 years. Hartmann´s procedure and ileostomy were the mainly reasons for restoration of intestinal continuity, representing together 87%. Termino-terminal anastomosis was performed in 71.8% of cases, by using mainly the manual technique. 25.6% developed complications, highlighting anastomotic leakage; there were three deaths (7.6%). The surgical time, the necessity of ICU and blood transfusion significantly related to post-operative complications. Conclusion : It was found that the majority of the patients were male, with an average age of 52 years. It was observed that the surgical time, the necessity of blood transfusion and ICU were factors significantly associated with complications.